2023
DOI: 10.1371/journal.pone.0281124
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT evaluation of frozen and embalmed human cadavers on the effect of root canal preparation on microcrack formation in old dentin

Abstract: The aim of this study was to evaluate the existence of preoperative dentinal defects among differently preserved dentoalveolar bone-blocks (frozen vs. embalmed) and to investigate the effect of varying apical forces (low: <4 N, high: 4–8 N) during root canal preparation on microcrack formation using micro-computed tomography (micro-CT). Thirteen embalmed and seven frozen bone-blocks containing 1–3 single rooted teeth were collected. The teeth were evenly divided into three groups (n = 10): FLow (frozen, <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…The impact of root canal preparation and its kinematics on crack formation has been widely studied with controversial results. [112][113][114] Recently, the impact of this clinical concern, and in general the importance of microcracks, often a common finding when analysing functional teeth in vivo, has been rejected as a crucial factor in the prognosis of root canal treated teeth. [115][116][117][118] Further, the apical extrusion of debris has been extensively investigated with different methodologies, mainly in in vitro studies.…”
Section: Reciprocating Movementmentioning
confidence: 99%
“…The impact of root canal preparation and its kinematics on crack formation has been widely studied with controversial results. [112][113][114] Recently, the impact of this clinical concern, and in general the importance of microcracks, often a common finding when analysing functional teeth in vivo, has been rejected as a crucial factor in the prognosis of root canal treated teeth. [115][116][117][118] Further, the apical extrusion of debris has been extensively investigated with different methodologies, mainly in in vitro studies.…”
Section: Reciprocating Movementmentioning
confidence: 99%
“…While there are many micro-CT studies investigating tumors in live and sacrificed animals [52][53][54][55][56][57][58][59][60][61][62][63][64][65], this technique can only be used for the examination of ex vivo specimens in the context of human tumors, since the radiation dose used in micro-CT examination is very high compared to a conventional CT [7,66,67]. Both fresh or formalin-fixed specimens can be successfully scanned with micro-CT [26,35,41,42,[68][69][70][71][72] (Figures 1-3; Supplementary Videos S1 and S2); however, the protocols to be employed need to be optimized to obtain the best results. In a study using fresh lung specimens, it was reported that artifacts caused by insufficient air-tissue contrast or tissue deflation could sometimes obscure the target lesion, but these artifacts could be reduced by making some adjustments to the protocol [26].…”
Section: Examination Steps In Which Micro-ct Can Be Usedmentioning
confidence: 99%